A mobile renewable house using PV/wind/fuel cell hybrid power system - DURSUN, ERKAN; KILIÇ, OSMAN (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
A photovoltaic/wind/fuel cell hybrid power system for stand-alone applications is proposed and demonstrated with a mobile house. This concept shows that different renewable sources can be used simultaneously to power off-grid applications. The presented mobile house can produce sufficient power to cover the peak load. Photovoltaic and wind energy are used as primary sources and a fuel cell as backup power for the system. The power budgeting of the system is designed based on the local data of solar radiation and wind availability. Further research will focus on the development of the data acquisition system and the implementation of automatic controls for power management. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Renewable energy; Photovoltaic (PV); Wind energy; Fuel cell; Hybrid power system; ENERGY SYSTEM; FUEL-CELL; STORAGE